2019
DOI: 10.1128/aem.00512-19
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Host Induces Antibiotic Production To Select the Most-Beneficial Colonizers

Abstract: Microbial ecosystems tightly associated with a eukaryotic host are widespread in nature. The genetic and metabolic networks of the eukaryotic hosts and the associated microbes have coevolved to form a symbiotic relationship. Both the Gram-positive Bacillus subtilis and the Gram-negative Serratia plymuthica can form biofilms on plant roots and thus can serve as a model system for the study of interspecies interactions in a host-associated ecosystem. We found that B. subtilis biofilms expand collectively and asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 93 publications
4
21
0
Order By: Relevance
“…In contrast, each of the induced antibiotics were shown to grant protection to the plant versus fungal and bacterial pathogens. Interestingly, we previously demonstrated that the interaction with the plant increases the capacity of B. subtilis to compete with Serattia Plymuthica, and our current results further indicate that the root is active regulator of the competitive interactions occurring on its roots (Ogran et al, 2019). The complexity of these antibiotic-host interactions suggests that B. subtilis biofilms can be considered a part of the plant microbiome, with the host actively promoting the establishment of the most beneficial bacterial community.…”
Section: Discussionsupporting
confidence: 70%
“…In contrast, each of the induced antibiotics were shown to grant protection to the plant versus fungal and bacterial pathogens. Interestingly, we previously demonstrated that the interaction with the plant increases the capacity of B. subtilis to compete with Serattia Plymuthica, and our current results further indicate that the root is active regulator of the competitive interactions occurring on its roots (Ogran et al, 2019). The complexity of these antibiotic-host interactions suggests that B. subtilis biofilms can be considered a part of the plant microbiome, with the host actively promoting the establishment of the most beneficial bacterial community.…”
Section: Discussionsupporting
confidence: 70%
“…Instead, we found that specific inhibition of ECM production inhibited normal biofilm development and limited colony spreading. In biofilms, bacteria frequently migrate towards new niches by sliding, powered by cell division and ECM production 8,15,54 . Blocking this collective motility may serve as an effective strategy to distance competitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, in many instances, biofilms can be beneficial. One example is the biocontrol agents that form biofilms on the surface of plant roots, producing antibiotics that prevent the growth of bacterial and fungal pathogens and inducing the plant systemic response [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of flagella allows the bacterium to swim and swarm, but the flagellum-independent sliding occurs due to growth 25 . Sliding is a poorly understood process, but it is known to depend upon multiple factors, such as the production of surfactin and/or the extracellular proteins BslA and TasA 25 27 .…”
Section: Introductionmentioning
confidence: 99%